Decrease in horn size and increase in age of trophy sheep in Alberta over 37 years. Issue 1 (5th December 2013) - Festa‐Bianchet, Marco; Pelletier, Fanie; Jorgenson, Jon T.; Feder, Chiarastella; Hubbs, Anne
ABSTRACT Long‐term data (1974–2011) from harvested bighorn rams (Ovis canadensis) in Alberta, Canada, suggested a reduction in horn size and in the proportion of trophy rams in the provincial population over time. Age at harvest increased over time, suggesting slower horn growth. Rams that experienced favorable environmental conditions early in life had rapid horn growth and were harvested at a younger age than rams with slower horn growth. Guided nonresident hunters did not harvest larger rams than residents, suggesting that few large rams were available. Resident hunter success declined in recent years. Despite an apparently stable population, successive cohorts produced a decreasing harvest of trophy rams. We suggest that unrestricted harvest based on a threshold horn size led to a decline in the availability of trophy rams. That decline is partly an inevitable consequence of selective hunting that removes larger rams. Although our analysis does not establish that evolution of smaller horns caused the observed decline in both horn size and harvest of trophy rams, we suggest that intensive trophy hunting may have artificially selected for a decrease in horn growth rate. © 2013 The Wildlife Society.